RELATIONSHIP OF CHOLESTEROL LEVEL AND BLOOD PRESSURE ON HYPERTENSION PATIENTS AT PUSKESMAS LOA BAKUNG - Noorhayaty, Noorhayaty; Wirapuspita Wisnuwardani , Ratih (HEARTY, 2025)
Hypertension is a non-transmissible disease that poses a health problem and is often found in basic healthcare facilities. One of the risk factors for hypertension is high total cholesterol levels. The purpose of this study is to analyze the correlation between cholesterol levels and blood pressure on hypertensive patients at Puskesmas Loa Bakung (Loa Bakung Community Health Center). This study utilizes descriptive-analytical observational cross-sectional method. The population in this study is hypertensive patients at the Puskesmas Loa Bakung. The sample data used in this study consists of all hypertension patients who came for blood tests in November 2024. The sample size was 67 people. The data was analyzed using the Spearman correlation test. The p-values for systolic and diastolic blood pressures are 0.232 and 0.483, respectively. The result shows no significant correlation between cholesterol levels and the occurrence of hypertension.